2008
DOI: 10.1124/jpet.108.140079
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Herkinorin, the First μ-Selective Ligand from a Salvinorin A-Derived Scaffold, in a Neuroendocrine Biomarker Assay in Nonhuman Primates

Abstract: Herkinorin is the first -opioid receptor-selective ligand from the salvinorin A diterpenoid scaffold. Herkinorin has relative Ͼ Ͼ ␦ binding selectivity, and it can act as an agonist at both -and -receptors, in vitro. These studies were the first in vivo evaluation of the effects of herkinorin in nonhuman primates, using prolactin release, a neuroendocrine biomarker assay that is responsive to both -and -agonists, as well as to compounds with limited ability to cross the blood-brain barrier. In cumulative dosin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 25 publications
0
13
0
Order By: Relevance
“…This action proved useful in generating a cellular system with which to facilitate the identification of neutral MOP receptor antagonists (Sally et al, 2010). Studies in nonhuman primates provided neuroendocrine evidence for both MOP agonist and partial KOP agonist effects of herkinorin (Butelman et al, 2008). It is clear that more studies must be initiated to facilitate understanding of this unique ligand.…”
Section: Pharmacological Evaluation Of Herkinorinmentioning
confidence: 99%
“…This action proved useful in generating a cellular system with which to facilitate the identification of neutral MOP receptor antagonists (Sally et al, 2010). Studies in nonhuman primates provided neuroendocrine evidence for both MOP agonist and partial KOP agonist effects of herkinorin (Butelman et al, 2008). It is clear that more studies must be initiated to facilitate understanding of this unique ligand.…”
Section: Pharmacological Evaluation Of Herkinorinmentioning
confidence: 99%
“…The development of ligands that activate ERK in the absence of β-arrestin–MOP receptor interactions may provide valuable tools for studying this pharmacology further and could possibly lead to the discovery of novel compounds for the treatment chronic pain. Additional studies in non-human primates showed that herkinorin has opioid receptor mediated effects using prolactin release, a neuroendocrine biomarker assay that is responsive to both MOP and KOP agonists, as well as to compounds with limited ability to cross the blood-brain barrier (Butelman et al, 2008). More recently, we described three new derivatives of herkinorin with similar properties and one that promotes recruitment of β-arrestin-2 to the MOP receptor and receptor internalization (Tidgewell et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, herkinorin is the first non-opioid mu opioid receptor ligand (Butelman et al, 2008). Herkinorin was discovered in 2005 when various analogues of the natural product Salvinorin A were synthesized to study the structure and the function of neoclerodane diterpenes (Harding et al, 2005; Tidgewell et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Herkinorin is the first non-opioid mu agonist derived from the structurally related compound salvinorin A (Butelman et al, 2008). Since kappa opioid receptor activation elicits pial artery dilation (Armstead, 1998) and salvinorin A is a potent cerebral vasculature dilator that activates nitric oxide synthases, kappa receptors, and adenosine triphosphate-sensitive potassium channels (Su et al, 2011), it is likely that herkinorin could also elicit cerebrovasodilation.…”
Section: Introductionmentioning
confidence: 99%